Noise performance of classical current mirrors - Alves, L. N.
This paper presents a comparison between six classical CM regarding noise considerations. This comparison is made based on analytical and simulation results, taking into account mostly thermal noise. As a result, the paper presents some design guidelines in order for achieving the design of low noise CM configurations. © 2002 IEEE.